The Efficacy of the Combination of 2% Lidocaine and 0,5% Bupivacaine as Preemptive Analgesia for post-operative pain in vitrectomy with or without scleral buckle under genral anasthesia - Marlyna Afifudin, Hartono, Angela Nurini Agni (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2009)
Background: Post-operative pain is one of the main problems in the surgical services so that analgesia is very much needed, even intravenously given. The concept of preemptive analgesia in surgical intervention is the provision of analgesia before the occurence of nociceptive stimulus. One of the agents for providing preemptive analgesia is local injection is local injection with local anasthetic, single or in combination. Objective: This study was aimed to evaluate the efficacy of combination of lidocain and bupivacain as preemptive analgesia in vitrectomy with or without sclera buckle under general anesthesia. Methods: Twenty eight patients who were scheduled for vitrectomy were included in this study. The patients were randomly classified into two equal groups. The surgery was conducted under general anesthesia for both groups, but in Group 1, subtenon anesthesia with local anesthetic was given as preemptive analgesia after induction anesthesia and before the start of surgery. Pain intensity was the primary outcome of this study. The pain intensity was measured in 3 hours and 24 hours after surgical procedure. Results: The baseline characteristics between the two groups were similar. The pain intensity was lower in the treatment group, but the difference was not statistically significant (1.00:t 1.71 vs 1.50:t 2.16, p = 0.109). The proportion of pain-free patients were similar between the two groups in 3 hours after procedure (65% vs 65%, p = 1.00). The proportion of pain-free patients were higher in the treatment group in 24 hours after procedure (100% vs 73%, p = 0.222, Fisher's Exact Test}. The subtenon injection procedure was safe. There was insignificant difference in the incidence of side effects between the 2 groups. Conclusion: This study did not show any additional benefit of subtenon injection for vitrectomy. The pain intensity was similar between two groups. There were no increases on side effects after the procedure. Key words: vitrectomy - local anesthetic - post-operative pain - preemptive analgesia